A characterisation study of Ubaid period ceramics from As‐Sabbiya, Kuwait, using a non‐destructive portable X‐Ray fluorescence (pXRF) spectrometer and petrographic analyses. (24th November 2019) - Ashkanani, Hasan J.; Tykot, Robert H.; Al‐Juboury, Ali Ismail; Stremtan, Ciprian C.; Petřík, Jan; Slavíček, Karel
Abstract : The Ubaid cultural phenomena (6500–4200 BC) of southern Mesopotamia has been used to characterise other archaeological sites in the Arabian Gulf region. The aim of this inquiry is to explore the nature of the interaction between the homeland of the Ubaid and the wider Gulf region. Through the use of a non‐destructive portable X‐ray fluorescence (pXRF) spectrometer, this study seeks to characterise and identify the chemical and mineralogical compositions of the ceramic assemblage from the Bahra 1 site of the As‐Sabbiya region, Kuwait. The chemical results demonstrated that a combination of six trace elements [rubidium (Rb), strontium (Sr), yttrium (Y), zirconium (Zr), niobium (Nb) and barium (Ba)] occur significantly enough to delineate clay‐based artifact groups—local red coarse from Ubaid, while the mineralogical analysis confirms the pXRF result and identifies the source of the raw materials and temper as well. Also, the comparison between the Ubaid and Bronze Age assemblage results suggests that potters used different clay resources within their own regions and/or production techniques.